Educating the Young Generation for Prospective Parenthood in the Context of Modern World Challenges - Nadejda OVCERENCO (Eastern European Journal of Regional Studies)
The purpose of the study is to investigate the problem of prospective parenting education for teenagers. The research is motivated by the decreased value of parenting and its impact on young people's conscience and behaviour. It analyzes the strategic plan of prospective parenting education at pre-university level, the school potential in the field under research and the evaluation of teachers' competences to cope with the problem of parenting for teenagers. Two strategies of capitalizing the school curricula regarding prospective parenting education for young people are examined and suggested as potential solutions for improvement.